Vascular access‐related mortality in hemodialysis patients during and after hospitalization. Issue 6 (26th February 2020) - Gil Giraldo, Yohana; Muñoz Ramos, Patricia; Ruano, Pablo; Quiroga, Borja
Abstract: Long‐term prognosis is poorer in hemodialysis patients wearing a permanent catheter than in those with a fistula; however, few data are available regarding the survival of hospitalized patients according to their vascular access. The aim of the present study is to analyze the influence of vascular access in the prognosis of hemodialysis patients during hospitalization. A prospective observational study was conducted, including 100 consecutive hemodialysis patients that were hospitalized for any cause. At baseline, we collected epidemiological data, comorbidities, and variables related to the hospitalization (analytical values, reason for admission, and type of vascular access). We divided the whole sample into two groups regarding the vascular access (fistula or catheter), and compared associated variables and short‐term survival. We analyzed mortality during hospitalization and during follow‐up. Of the 100 patients studied, 71 (71%) were male, with a mean age of 71 ± 12 years. Fifty patients (50%) had fistulae as vascular access. Mean dialysis vintage was 60 ± 47 months. Eighteen patients (18%) died during the hospitalization and 27 (27%) at the end of the follow‐up (median 144 [47‐269] months). Variables associated to survival during hospitalization were vascular access, personal history of heart failure, dialysis vintage, and analytical values at admission such as low hemoglobin, high lactic acid, and low albumin. A regression model demonstrated that vascular access was an independent predictor of survival during hospitalization and, also, during the follow‐up. Permanent catheters should be avoided as they are independent predictors of mortality in hospitalized hemodialysis patients.